Feedback control of chromosome separation by a midzone Aurora B gradient - Afonso, O (2014)
Accurate chromosome segregation during mitosis requires the physical separation of sister chromatids before nuclear envelope reassembly (NER). However, how these two processes are coordinated remains unknown. Here, we identified a conserved feedback control mechanism that delays chromosome decondensation and NER in response to incomplete chromosome separation during anaphase. A midzone-associated Aurora B gradient was found to monitor chromosome position along the division axis and to prevent premature chromosome decondensation by retaining Condensin I. PP1/PP2A phosphatases counteracted this gradient and promoted chromosome decondensation and NER. Thus, an Aurora B gradient appears to mediate a surveillance mechanism that prevents chromosome decondensation and NER until effective separation of sister chromatids is achieved. This allows the correction and reintegration of lagging chromosomes in the main nuclei before completion of NER.